Differences in structure and distribution of the molecular forms of acetylcholinesterase (The Rockefeller University Press, 1989)
Two structurally distinct molecular forms of acetylcholinesterase are found in the electric organs of Torpedo californica. One form is dimensionally asymmetric and composed of heterologous subunits. The other form is hydrophobic and composed of homologous subunits. Sequence- specific antibodies were raised against a synthetic peptide corresponding to the COOH-terminal region (Lys560-Leu575) of the catalytic subunits of the asymmetric form of acetylcholinesterase. These antibodies reacted with the asymmetric form of acetylcholinesterase, but not with the hydrophobic form. These results confirm recent studies suggesting that the COOH-terminal domain of the asymmetric form differs from that of the hydrophobic form, and represent the first demonstration of antibodies selective for the catalytic subunits of the asymmetric form. In addition, the reactive epitope of a monoclonal antibody (4E7), previously shown to be selective for the hydrophobic form of acetylcholinesterase, has been identified as an N-linked complex carbohydrate, thus defining posttranslational differences between the two forms. These two form- selective antibodies, as well as panselective polyclonal and monoclonal antibodies, were used in light and electron microscopic immunolocalization studies to investigate the distribution of the two forms of acetylcholinesterase in the electric organ of Torpedo. Both forms were localized almost exclusively to the innervated surface of the electrocytes. However, they were differentially distributed along the innervated surface. Specific asymmetric-form immunoreactivity was restricted to areas of synaptic apposition and to the invaginations of the postsynaptic membrane that form the synaptic gutters. In contrast, immunoreactivity attributable to the hydrophobic form was selectively found along the non-synaptic surface of the nerve terminals and was not observed in the synaptic cleft or in the invaginations of the postsynaptic membrane. This differential distribution suggests that the two forms of acetylcholinesterase may play different roles in regulating the local concentration of acetylcholine in the synapse.